The Internet's Coming of Age - National Research Council
What most of us know as \

Embedded, Everywhere: A Research Agenda for Networked Systems of Embedded Computers - National Research Council (The National Academies Press, 2001)
Advances in the miniaturization and networking of microprocessors promise a day when networked computers are embedded throughout the everyday world. However, our current understanding of what such systems would be like is insufficient to bring the promise to reality. Embedded, Everywhere explores the potential of networked systems of embedded computers and the research challenges arising from embedding computation and communications technology into a wide variety of applications2014from precision agriculture to automotive telematics to defense systems. It describes how these emerging networks operate under unique constraints not present in more traditional distributed systems, such as the Internet. It articulates how these networks will have to be dynamically adaptive and self-configuring, and how new models for approaching programming and computation are necessary. Issues relating to trustworthiness, security, safety, reliability, usability, and privacy are examined in light of the ubiquitous nature of these systems. A comprehensive, systems-oriented research agenda is presented, along with recommendations to major federal funding agencies.

Summary of Discussions at a Planning Meeting on Cyber-Security and the Insider Threat to Classified Information - National Research Council (The National Academies Press, 2001)
This is a summary of discussions at a planning meeting held November 1-2, 2000 to examine the prospects of initiating an NRC study on cyber-security and the insider threat to classified information. The meeting's focus was on the threat to classified systems and information because the political and organizational issues that often arise with protection policies and practices (e.g., rights to privacy) are considerably fewer and less intense than if sensitive unclassified information (especially non-governmental information) is involved. The meeting also addressed threats other than insider threats as well as non-classified computer systems.